2022
DOI: 10.3390/vaccines10070993
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Preventable Zoonotic Diseases: Challenges and Opportunities for Public Health Progress

Abstract: Zoonotic diseases represent a heavy global burden, causing important economic losses, impacting animal health and production, and costing millions of human lives. The vaccination of animals and humans to prevent inter-species zoonotic disease transmission is an important intervention. However, efforts to develop and implement vaccine interventions to reduce zoonotic disease impacts are often limited to the veterinary and agricultural sectors and do not reflect the shared burden of disease. Multisectoral collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 107 publications
0
27
0
Order By: Relevance
“…Results from the study also showed that the actors have practices such as separating sick animals from the rest, not allowing sick animals in the market, and vaccinating their animals, which can prevent the animals from spreading diseases ( 60 62 ). Unlike other studies that have shown that pastoralists self-medicate their animals for different reasons, like having high confidence in their abilities and low confidence in the skills of animal health service providers, limited access to animal health service providers, and high cost ( 63 65 ) this study found that the livestock traders engage the help of those that they perceive to be animal health experts whenever they identify that their animal is sick.…”
Section: Discussionmentioning
confidence: 94%
“…Results from the study also showed that the actors have practices such as separating sick animals from the rest, not allowing sick animals in the market, and vaccinating their animals, which can prevent the animals from spreading diseases ( 60 62 ). Unlike other studies that have shown that pastoralists self-medicate their animals for different reasons, like having high confidence in their abilities and low confidence in the skills of animal health service providers, limited access to animal health service providers, and high cost ( 63 65 ) this study found that the livestock traders engage the help of those that they perceive to be animal health experts whenever they identify that their animal is sick.…”
Section: Discussionmentioning
confidence: 94%
“…IAVs, coronaviruses, rabies, and brucellosis are the most common zoonotic diseases that can be transmitted from animals to humans through zoonotic spillover, posing a threat to public health. [ 181 ] Table 2 summarizes representative cases of the application of nanotechnology in the design of vaccines against zoonotic diseases. In conclusion, nanotechnology promotes the development of animal vaccines in multiple ways.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the diseases in the world are caused by the zoonotic aspect and usually animal turns into one of the agents with various way to deliver it as being bitten or consuming them (Rahman et al, 2020); (Bauer, Zhang, & Linhardt, 2021), Warm-blooded birds and mammals usually become one of the most easily infected hosts (Angel et al, 2020) Saldarriaga Cartagena, & Sullivan Jr, 2020. Either pandemic or endemic are not only considered as infectious but also dangerous due to the spread speed, how they spread are usually through fluid, physical contact and consuming the hosts or surfaces (Morens & Fauci, 2020;(Valencia, 2020) Tomohon is well-known as a city which sells extreme cuisine with various unusual meats such as cats, dogs, rats, wild boards, snakes, pigs, bats etc (Tamboto, Tambingon, Lengkong, & Rotty, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Either pandemic or endemic are not only considered as infectious but also dangerous due to the spread speed, how they spread are usually through fluid, physical contact and consuming the hosts or surfaces (Morens & Fauci, 2020;(Valencia, 2020) Tomohon is well-known as a city which sells extreme cuisine with various unusual meats such as cats, dogs, rats, wild boards, snakes, pigs, bats etc (Tamboto, Tambingon, Lengkong, & Rotty, 2021). As mentioned before, some foods basically can be an agent for zoonotic parasites to spread and there were cases as coronavirus was spread initially from Seafood Market (Valencia, 2020), avian influenza through the contact and consumption of the poultries (Phan et al, 2020) Due to the breakouts, there are lots of preventions that are done to vaccinate the agent or infected humans (Carpenter et al, 2022). But that does not mean that all of the animals including the wild animals will get vaccinated, it is said that most of the supply on Tomohon market is basically being taken from the wildlife which we cannot reassure if the species were all being vaccinated which would elevate a potential risk to human health and might turn into an endemic (Gao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%